A Comparative Study on Different Types of Contracts Operating in Derivatives Market in India - B, Ganesh; V , Velmurugan; K, Arun B (International Journal of Psychosocial Rehabilitation, 2020)
In financial terms, different methods of investments and depositing are termed as “instruments” and such of the instruments where there are specific rights and obligations are termed as “Contracts”. A Derivative is an instrument whose value is derived from the value of underlying assets with respect to changes happening over a period of time. The assets that give rise to derivatives range from commodities to stocks. The term “derivative” refers to the likely movement of a commodity price or a share prices at a future date. Thus, derivatives depend on the investment made by the investors with respect to likely future price state. Over a period of time as the derivatives market progressed different types of participants emerged and to facilitate them different types of contracts were devised. The present study is based on the two research questions – “What are different types of contracts that are prevalent in Indian derivatives market? and “What are preferences for different types of contracts by different types of participants in Indian derivatives market”. The study adopts both primary and secondary data collected from different and associated sources. The data so collected were analyzed by employing tabulation and comparison methods. The study, concludes that as the time progresses, the Indian derivatives market would see further differentiation among the different types of participants. Further, the study predicts that there will be further fine- tuning of the contracts in Indian derivatives market. Suggestions, Recommendations and Scope for future research were listed at the end of the research paper.